The Effects of Internet-Delivered Mindfulness Training on Stress, Coping, and Mindfulness in University Students - David Messer; John J. Horan; Wesley Turner; Wanda Weber (SAGE Publishing, 2015)
Internet-delivered mindfulness and relaxation training were compared with each other and a no-treatment control on stress, coping, and mindfulness measures. Participants ( n = 114) were assessed before and after treatment, and their compliance with the intervention they received was tracked. The treatments were received at a time, place, and computer of the participants' choosing with the proviso that three exercises be completed during each of three successive weeks. Both mindfulness and relaxation reduced stress, but only mindfulness training increased mindfulness and reduced emotion-focused coping.